Analisis Kemampuan Berpikir Kritis Siswa Sma Melalui Model Inquiry Based Learning Berbantuan Media Wayang Sukuraga Pada Materi Sistem Indra: (Analysis of Critical Thinking Ability of High School Students Through an Inquiry-Based Learning Model Assisted by Wayang Sukuraga Media on The Material) - Putri Ajeng Dwi Cahyani; Setiono Setiono; Aa Juhanda (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
This study aims to analyze the critical thinking ability of high school students using the Inquiry Based Learning model assisted by sukuraga puppet media on the sensory system material.Â This studyÂ used a study sample of 35 students.Â The type of research used in this study is pre-experimental with a pretest posttest one group design research design.Â This research was conducted as many as 2 meetings using the Inquiry Based Learning learning model assisted by Wayang Sukuraga media.Â The research instruments used are 8 items of description questions with indicators that include 5 indicators of critical thinking, namely 1) Providing simple explanations, 2) Making further explanations, 3) Building basic skills, 4) Making inferences, 5) Setting strategies and techniques.Â The results showed an increase after being given treatment for students' critical thinking abilities.Â This can be seen by the increase in posttest results based on 5 critical thinking indicators of 85.8.Â The N-Gain score in this study was 0.64 which belonged to the